Nasopharyngeal Carriage of Antimicrobial-Resistant Pneumococci in an Intensively Sampled South African Birth Cohort - Manenzhe, Rendani I.; Moodley, Clinton; Abdulgader, Shima M.; Robberts, F. J. Lourens; Zar, Heather J.; Nicol, Mark P.; Dube, Felix S. (Frontiers in Microbiology, 2019)
Nasopharyngeal (NP) colonization by Streptococcus pneumoniae (pneumococcus) precedes the development of respiratory tract infection. Colonization by antimicrobial-resistant pneumococci, especially in infants, is a major public health concern. We longitudinally investigated antimicrobial-resistance amongst pneumococci colonizing the nasopharynx of South African infants immunized with the 13-valent pneumococcal conjugate vaccine (PCV13). NP swabs were collected every second week from birth through the first year of life from 137 infants. Pneumococci were identified and serotyped using conventional microbiological techniques, and their antibiotic susceptibility profiles determined by disc diffusion and E-test. All infants were immunized with 3 doses of PCV13. 1520 pneumococci (760 non-repeat) isolates were recovered from 137 infants; including non-typeable (n = 99), PCV13 (n = 133) and non-PCV13 serotypes (n = 528). The prevalence of penicillin, erythromycin, and cotrimoxazole non-susceptibility was 19% (95% CI 17-22%) (3% fully-resistant), 18% (95% CI 15-21%) (14% fully-resistant) and 45% (95% CI 42-49%) (36% fully-resistant) respectively. The predominant penicillin-non-susceptible serotypes included 19A, 19F, 15B/15C, 15A and 21, while susceptible serotypes included 23A, 34, and 17A. Multidrug-resistance (MDR) was observed in 9% (95% CI 7-11%) of the isolates. PCV13 serotypes were more likely to be non-susceptible, compared to non-PCV13 serotypes, to penicillin (26% vs. 16%, p = 0.007), erythromycin (23% vs. 15%, p = 0.027) and cotrimoxazole (62% vs. 41%, p < 0.001). Non-susceptibility to penicillin, erythromycin, and cotrimoxazole remained relatively constant through the first year of life (X2 test for trend: p = 0.184, p = 0.171, and p = 0.572, respectively). Overall, penicillin or erythromycin-non-susceptible pneumococci were carried for a shorter duration than susceptible pneumococci (penicillin [mean days, 18 vs. 21, p = 0.013] and erythromycin [mean days, 18 vs. 21, p = 0.035]). Within individual infants carrying the same serotype longitudinally, changes in antibiotic susceptibility were observed over time in 45% (61/137) of infants and these changes were predominantly for penicillin (76%, 79/104). Prevalence of NP carriage with antibiotic-non-susceptible pneumococci was relatively constant throughout the first year of life. PCV13 serotypes were more commonly non-susceptible to penicillin, erythromycin, and cotrimoxazole. Penicillin or erythromycin-non-susceptible pneumococci were carried for a shorter duration than penicillin or erythromycin-susceptible pneumococci.